Introduction to Special Issue on Gender and Leadership and a Future Research Agenda - Pat O'Connor (MDPI AG, 2018)
Despite the feminisation of universities in terms of their student intake [1,2], formal positions of academic leadership in higher education remain concentrated in male hands[…]